Contrast-enhanced ultrasound as a valuable tool to detect minimal inflammation in RA patients in sustained remission - Polido-Pereira, Joaquim; António, Manuel S.; Khmelinskii, Nikita; Arese, Marta; Teixeira, Rui; Vieira-Sousa, Elsa; D'Agostino, Maria A.; Fonseca, João E. (Frontiers in Medicine, 2024)
Objective: The study aimed to explore the utility of contrast-enhanced ultrasound (CEUS) as a tool for detecting minimal inflammation in rheumatoid arthritis (RA) patients in sustained remission (SR) and to correlate findings with Disease Activity Score 28 (DAS28) status scores and various ultrasound (US) scores.Patients and Methods: Thirty RA patients in SR (minimum 6 months), 12 with active disease, and 10 healthy controls were included. Clinical evaluations and US assessments were performed, including greyscale US (GSUS), power Doppler US (PDUS), and Global OMERACT-EULAR synovitis score (GLOESS). CEUS was performed in the two most active joints and was scored semiquantitatively (SQ) and quantitatively.Results: Healthy controls and remission RA patients had similar total US scores. Active RA patients had higher US scores than healthy and remission groups, with statistically significant differences in all groups compared to healthy but only in GSUS and GLOESS when compared with remission.Ninety-five joints were selected for CEUS, and we detected more microvascularisation with the SQ CEUS score than with PDUS in all groups (18 vs 58% in the remission group; p-value 0.006). The weighted Cohen's kappa for intra-rater and inter-rater IACUS CEUS score was 0,714 (confidence interval 0,610-0,819, p-value <0,001) and 0,540 (confidence interval 0,419-0,662, p-value <0,001), respectively. The Spearman's correlation between the SQ CEUS and quantitative score was 0.655.For most RA patients in SR, conventional US may fail to detect microvascularisation potentially related to the subclinical disease. CEUS may be helpful for this purpose.